Hubungan Personal Hygiene dan Kepatuhan ANC dengan Kekurangan Energi Kronis pada Ibu Hamil - Hafizhah, Najwa Zahra; Stellata, Alyxia Gita; Dariani, Lili (Jurusan Kebidanan Poltekkes Kemenkes Padang, 2024)
Chronic Energy Deficiency (CED) among pregnant women remains a public health issue in Agam Regency. A preliminary survey at Lubuk Basung Health Center showed that 13.33% of pregnant women experienced CED, although ANC coverage in the Polindes Jorong II Balai Ahad area had reached 91%. This indicates that other factors may influence the incidence of CED, such as poor personal hygiene, ANC non-compliance, low nutritional knowledge, and socioeconomic factors. This study aimed to identify factors associated with CED among pregnant women, including personal hygiene, ANC compliance, parity, income, and nutritional knowledge. This quantitative study used a cross-sectional design conducted from January to May 2025 in the working area of Polindes Jorong II Balai Ahad, Lubuk Basung, Agam Regency. The sample consisted of 60 pregnant women selected using a total sampling technique. Data were collected through questionnaires, interviews, and Mid-Upper Arm Circumference (MUAC) measurements, and analyzed using the chi-square test (p < 0.05). The results showed that 6.7% of pregnant women experienced CED. There was a significant relationship between personal hygiene (p = 0.022) and ANC compliance (p = 0.027) with CED, while parity, income, and nutritional knowledge were not significant.